Professional Competence of Arabic Language Teachers Based on the National Education Standards - Isop Syafei; Ade Arip Ardiansyah (Gunung Djati Conference Series, 2025)
This study aims to analyze the professional competence of Arabic language teachers based on the National Education Standards (NES). It employs a descriptive qualitative approach to provide an in-depth portrayal of Arabic language teachers’ professional competence in accordance with the NES. Primary data were obtained through interviews and observations, while secondary data were sourced from official documents. Data collection techniques included in-depth interviews, participatory observation, and document analysis. Data analysis followed the interactive model of Miles, Huberman, and Saldana, incorporating source, method, and time triangulation to ensure the validity and credibility of the findings. The results indicate that Arabic language teachers play a vital role in improving education quality in line with the NES through mastery of language materials both theoretically and practically, language skills, and the development of relevant teaching materials. They integrate Arab-Islamic culture, utilize educational technology, and conduct Classroom Action Research to improve teaching methods. With these competencies, teachers can create effective, adaptive, and relevant learning environments, thus achieving the optimal goals of Arabic language education. The findings suggest that Arabic language teachers should continuously enhance their professional competence through ongoing training, the use of educational technology, and the development of contextual learning materials. Strengthening the integration of Arab-Islamic cultural values and the application of Classroom Action Research is essential for refining teaching strategies. These efforts will contribute to the creation of effective, adaptive, and contemporary learning, thereby optimizing the achievement of Arabic language learning objectives.